PAR1 participates in the ability of multidrug resistance and tumorigenesis by controlling Hippo-YAP pathway - Fujimoto, Daisuke (Oncotarget, 2015)
The Hippo pathway significantly correlates with organ size control and tumorigenesis. The activity of YAP/TAZ, a transducer of the Hippo pathway, is required to sustain self-renewal and tumor-initiation capacities in cancer stem cells (CSCs). But, upstream signals that control the mammalian Hippo pathway have not been well understood. Here, we reveal a connection between the Protease-activated receptor 1 (PAR1) signaling pathway and the Hippo-YAP pathway in gastric cancer stem-like cells. The selective PAR1 agonist TFLLR-NH(2) induces an increase in the fraction of side population cells which is enriched in CSCs, and promotes tumorigenesis, multi cancer drug resistance, cell morphological change, and cell invasion which are characteristics of CSCs. In addition, PAR1 activation inhibits the Hippo-YAP pathway kinase Lats via Rho GTPase. Lats kinase inhibition in turn results in increased nuclear localization of dephosphorylated YAP. Furthermore, PAR1 activation confers CSCs related traits via the Hippo-YAP pathway, and the Hippo-YAP pathway correlates with epithelial mesenchymal transition which is induced by PAR1 activation. Our research suggests that the PAR1 signaling deeply participates in the ability of multi drug resistance and tumorigenesis through interactions with the Hippo-YAP pathway signaling in gastric cancer stem-like cells. We presume that inhibited YAP is a new therapeutic target in the treatment human gastric cancer invasion and metastasis by dysregulated PAR1 or its agonists. The Hippo pathway significantly correlates with organ size control and tumorigenesis. The activity of YAP/TAZ, a transducer of the Hippo pathway, is required to sustain self-renewal and tumor-initiation capacities in cancer stem cells (CSCs). But, upstream signals that control the mammalian Hippo pathway have not been well understood. Here, we reveal a connection between the Protease-activated receptor 1 (PAR1) signaling pathway and the Hippo-YAP pathway in gastric cancer stem-like cells. The selective PAR1 agonist TFLLR-NH(2) induces an increase in the fraction of side population cells which is enriched in CSCs, and promotes tumorigenesis, multi cancer drug resistance, cell morphological change, and cell invasion which are characteristics of CSCs. In addition, PAR1 activation inhibits the Hippo-YAP pathway kinase Lats via Rho GTPase. Lats kinase inhibition in turn results in increased nuclear localization of Dephosphorylated YAP. Furthermore, PAR1 activation confers CSCs related traits via the Hippo-YAP pathway, and the Hippo-YAP pathway correlates with epithelial mesenchymal transition which is induced by PAR1 activation. Our research suggests that the PAR1 signaling deeply participates in the ability of multi drug resistance and tumorigenesis through interactions with the Hippo-YAP pathway signaling in gastric cancer stem-like cells. We presume that inhibited YAP is a new therapeutic target in the treatment human gastric cancer invasion and metastasis by dysregulated PAR1 or its agonists.